Measures of Language Proficiency in Censuses and Surveys A Comparative Analysis and Assessment - Ó Riagáin, Pádraig (Springer International Publishing, 2018)
This book offers a systematic analysis of a wide range of questions used in censuses, national surveys and international surveys to measure language proficiency. It addresses the urgent need in language related survey research for a comprehensive examination of the large existing body of survey data in order to provide a fuller understanding of the extent to which survey results are shaped by the way language proficiency questions are shaped and worded. While census and survey language proficiency data are extensively used in a wide range of research areas, as well as in forming, implementing and monitoring government policies, there are as yet no universally accepted survey measures of language proficiency. This book will therefore provide a valuable resource for students and scholars working in sociological areas that use census or survey language data, such as sociology of language, sociology of education, politics, racial and ethnic studies, and cultural studies; as well as for policy analysts.